Role of cryogenic processes in the organization of soils at macro-, mesoand micro-levels - S. V. Gubin (Бюллетень Почвенного института им. В.В. Докучаева)
Cryogenic processes that occur in permafrost-affected and perennially frozen soils are analyzed and systematized. Their influences are observed at the three levels of soil organization. Thin sections are prepared from thawed and frozen soil samples.